2008
DOI: 10.1186/1471-2164-9-168
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome comparative studies between chicken and turkey and their implications for avian genome evolution

Abstract: Background: Comparative genomics is a powerful means of establishing inter-specific relationships between gene function/location and allows insight into genomic rearrangements, conservation and evolutionary phylogeny. The availability of the complete sequence of the chicken genome has initiated the development of detailed genomic information in other birds including turkey, an agriculturally important species where mapping has hitherto focused on linkage with limited physical information. No molecular study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
140
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(161 citation statements)
references
References 40 publications
16
140
3
2
Order By: Relevance
“…Nearly 85 % of the probes hybridized to quail LBCs in our experiments. This efficiency of heterologous hybridization corresponds to that previously observed for FISH with large-size chicken probes on metaphase chromosomes from different galliform species (Shibusawa et al 2001(Shibusawa et al , 2002Kasai et al 2003;Schmid et al 2005;Kayang et al 2006;Griffin et al 2008). The high-resolution comparative FISH mapping combined with fine detection of centromere positions on lampbrush chromosomes allows us to determine gene order relative to centromeres most precisely.…”
Section: Resultssupporting
confidence: 81%
“…Nearly 85 % of the probes hybridized to quail LBCs in our experiments. This efficiency of heterologous hybridization corresponds to that previously observed for FISH with large-size chicken probes on metaphase chromosomes from different galliform species (Shibusawa et al 2001(Shibusawa et al , 2002Kasai et al 2003;Schmid et al 2005;Kayang et al 2006;Griffin et al 2008). The high-resolution comparative FISH mapping combined with fine detection of centromere positions on lampbrush chromosomes allows us to determine gene order relative to centromeres most precisely.…”
Section: Resultssupporting
confidence: 81%
“…Similarly, overall karyotype structure is highly conserved in birds, with the vast majority of extant species displaying a karyotype with about 2n = 80 chromosomes, comprising few macro-and many small microchromosomes, and a ZZ/ZW sex chromosome pair (Christidis 1990;Rodionov 1997;Griffin et al 2007). In line with the above data, recent studies of CNVs in turkey and duck (relative to chicken) have suggested that bird genomes also contain a low number of CNVs compared to mammalian genomes (Griffin et al 2008;Skinner et al 2009). Recombination rates in chicken and zebra finch, the only two bird species for which there is information on absolute rates of recombination (The International Chicken Genome Sequencing Consortium 2004; Groenen et al 2009;Backström et al 2010), are higher overall than in mammals.…”
supporting
confidence: 68%
“…A special case is represented by chromosome 4 where the highest recombination rate, GC content, and cohesion density is observed within the p-arm of this chromosome. Interestingly, a comparison between the karyotypes of chicken, turkey, and other birds indicates that chicken chromosome 4 is the result of a fusion between a macrochromosome and a microchromosome in the lineage leading to chicken (Griffin et al 2008). The density plots for chromosome 4 shown in Figure 4 provide further support for the microchromosomal origin of the p-arm of this chromosome.…”
Section: Discussionmentioning
confidence: 85%